Discretionary Disclosures to Risk‐Averse Traders: A Research Note - Jorgensen, Bjorn N.; Kirschenheiter, Michael T. (Contemporary Accounting Research, 2015)
Verrecchia (1983) investigates a manager's incentives for costly, discretionary disclosure of his information to risk‐averse traders when the functional form of prices is exogenously specified. We extend Verrecchia (1983) by deriving the endogenously determined functional form of prices that would arise when all traders have constant risk tolerance. We show that these endogenously determined prices are inconsistent with the assumed prices in Verrecchia (1983) when the manager elects to not disclose. We derive the manager's disclosure strategy for our setting and extend the comparative static results in Verrecchia (1990) for risk‐neutral traders to a setting where traders have constant risk tolerance and prices are endogenously derived. Further, in our setting, discretionary disclosure does not affect how traders price risk of different outcomes. Also, we offer a representation of risk‐averse traders' prices using risk‐adjusted distributions. Finally, these results provide implications for empirical‐archival discretionary disclosure studies.